Demand and Willingness to Pay for Rice Commodities In West Java - Adinda Elly Isnaini; Suprapti Supardi; Agustono Agustono (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Rice is the staple food of Indonesian people. In West Java, the price of rice in 2019 in the turn of the month increases gradually, therefore, more attention is needed regarding rice price stabilization. Price stabilization is an important dimension in contributing to social welfare stabilization. This study aimed to determine the factors that influence rice demand and consumers' willingness to pay for rice (Willingness to Pay) in West Java. The basic methods of this research were descriptive and analytical methods. The method of taking location was purposive and sampling was done by convenience sampling technique. Types of data and data sources were primary data and secondary data. Data collection techniques by interview, observation and recording. Data analysis methods used included: (1) Descriptive Analysis Method; (2) Analysis of factors that influence demand by using Seemingly Unrelated Regression (SUR); (3) Willingness to Pay (WTP). The results showed that the price of rice had a positive effect on rice expenditure, yet had a negative effect on rice demand. While the number of family members has a positive effect on rice demand. Calculation of value (WTP) obtained Gross WTP value of IDR 4,315,638.26. The amount to be paid is IDR 243,635.85, the Net WTP value is IDR 4,072,002.41. When prices increase by 10%. then the welfare level decreased by -67.89%. Meanwhile, when prices fell by 10%, the welfare level increased by 61.10%.